Factors Affecting Work Readiness of Vocational School Graduates: A Systematic Literature Review - Arik Harianto; Buwani Buwani; Erta Faradina; Tuwoso Tuwoso (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to identify and classify factors that influence the work readiness of vocational school graduates, analyze the contribution of each factor, and provide evidence-based recommendations for policy development and learning practices in vocational schools. The method used in this study is Systematic Literature Review (SLR), which analyzes articles related to factors affecting the work readiness of vocational school graduates from ScienceDirect. The results of the review show that the Work Readiness of vocational school graduates is influenced by three main categories of factors: individual (technical competence, soft skills, self-efficacy), institutional (curriculum, industrial practice experience), and external (industrial environment, local job opportunities, government policies). All three interact with each other and contribute significantly to work readiness. Strengthening work readiness can be achieved by adapting the curriculum that is relevant to labor market needs, increasing industrial practice experience, and strengthening institutional support and cooperation with the business world. Recommendations for vocational education policy development include improving curriculum quality, strengthening soft skills, and providing wider internship and career development opportunities.